2017
DOI: 10.3389/fnagi.2017.00078
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously Hypertensive Rats (SHR) Are Resistant to a Reserpine-Induced Progressive Model of Parkinson’s Disease: Differences in Motor Behavior, Tyrosine Hydroxylase and α-Synuclein Expression

Abstract: Reserpine is an irreversible inhibitor of vesicular monoamine transporter-2 (VMAT2) used to study Parkinson’s disease (PD) and screening for antiparkinsonian treatments in rodents. Recently, the repeated treatment with a low-dose of reserpine was proposed as a progressive model of PD. Rats under this treatment show progressive catalepsy behavior, oral movements and spontaneous motor activity decrement. In parallel, compared to Wistar rats, spontaneously hypertensive rats (SHR) are resistant to acute reserpine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 67 publications
4
14
0
Order By: Relevance
“…Corroborating previous studies, we observed that reserpine treatment induced a progressive motor impairment in male rats ( Fernandes et al, 2012 ; Santos et al, 2013 ; Leão et al, 2017 ; Lins et al, 2018 ; Bispo et al, 2019 ). Interestingly, male rats showed more susceptibility to these motor alterations than female rats.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Corroborating previous studies, we observed that reserpine treatment induced a progressive motor impairment in male rats ( Fernandes et al, 2012 ; Santos et al, 2013 ; Leão et al, 2017 ; Lins et al, 2018 ; Bispo et al, 2019 ). Interestingly, male rats showed more susceptibility to these motor alterations than female rats.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, Restreated rats, irrespective of sex, presented a significant decrease in motor activity 48 h after the 10th and 15th injections. In this regard, other studies have described similar effects for males (Santos et al, 2013;Leão et al, 2017;Lins et al, 2018;Bispo et al, 2019) and females (Bispo et al, 2019). Although there is a visually more pronounced reduction in locomotion in reserpine females than in males in the second open field session, statistical analysis did not show a significant interaction between time (repeated sessions) and sex.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations